2010
DOI: 10.1007/s12402-010-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SHR, WKY and Wistar rats in different behavioural animal models: effect of dopamine D1 and alpha2 agonists

Abstract: Spontaneously hypertensive rats (SHR) and its counterpart, the Wistar-Kyoto rats (WKY), are probably the most often used animal model of ADHD. However, SHR as model of ADHD have also been criticised partly because of not differing to outbred rat strains. In the present study, adolescent SHR, WKY and Wistar rats from Charles River were tested in open-field, elevated plus maze and novel object recognition and on gastrointestinal transport to more intensively evaluate the strain characteristics. Non-habituated SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 58 publications
4
34
1
1
Order By: Relevance
“…One possible mechanism is a reduction in noradrenergic neurotransmission, which is elevated in SHR and associated with high blood pressure and locomotor hyperactivity [62, 72]. In Epi-treated SHR rats, noradrenergic hyperfunction may be diminished by presynaptic α 2 -autoreceptor-mediated feedback [62, 73], the improvement of calcium signaling [62, 74], and/or increases in bioavailability of NO [75]. These effects may prevent hypertension development and decrease locomotion in young SHR.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is a reduction in noradrenergic neurotransmission, which is elevated in SHR and associated with high blood pressure and locomotor hyperactivity [62, 72]. In Epi-treated SHR rats, noradrenergic hyperfunction may be diminished by presynaptic α 2 -autoreceptor-mediated feedback [62, 73], the improvement of calcium signaling [62, 74], and/or increases in bioavailability of NO [75]. These effects may prevent hypertension development and decrease locomotion in young SHR.…”
Section: Discussionmentioning
confidence: 99%
“…In both the beginning and end periods of the exercise protocol, SHR presented better functional capacity than WKY rats. Previous studies have shown that SHR are more physically active, therefore presenting better functional capacity than normotensive rats [50,51]. Improved functional capacity in SHR occurred despite a slight increase in arterial blood pressure compared to SHR-SED.…”
Section: Discussionmentioning
confidence: 89%
“…The behavior of other models – such as the complete lack of stimulation found in the C57-congenic DAT-CI mice – is less similar to ADHD patients. A heavily studied rat model of ADHD notably lacks amphetamine’s calming effect (Langen and Dost, 2011). In this regard, the 129:C57 hybrid DAT-CI mice have good face and predictive validity as an ADHD animal model.…”
Section: Discussionmentioning
confidence: 99%